Space-time Functionalism: a Guide for the Perplexed - Picado Lara, Kevin (2024)
According to inertial frame functionalism, a structure will play the space-time role just in case it describes a structure of inertial frames. The present paper provides an introduction to the topic in the context of wider debates about the ontology of space-time assuming a minimal technical background.